Auxin induces redox regulation of ascorbate peroxidase 1 activity by S-nitrosylation/denitrosylation balance resulting in changes of root growth pattern in Arabidopsis - Correa Aragunde, Maria Natalia (2013)
S-nitrosylation of Cys-residues is one of the molecular mechanisms driven by nitric oxide (NO) for regulating biological functions of key proteins. While the studies on S-nitrosylation of Cys residues have served for identifying SNO-proteomes, the physiological relevance of protein S-nitrosylation/denitrosylation remains poorly understood. In this study, it is shown that auxin influences the balance of S-nitrosylated/denitrosylated proteins in roots of Arabidopsis seedlings. 2D-PAGE allowed the identification of ascorbate peroxidase 1 (APX1) as target of auxin-induced denitrosylation in roots. Auxin causes APX1 denitrosylation and partial inhibition of APX1 activity in Arabidopsis roots. In agreement, the S-nitrosylated form of recombinant APX1 expressed in E. coli is more active than the denitrosylated form. Consistently, Arabidopsis apx1 mutants have increased H2O2 accumulation in roots, shorter roots and less sensitivity to auxin than the wild type. It is postulated that an auxin-regulated counterbalance of APX1 S-nitrosylation/denitrosylation contributes to a fine-tuned control of root development and determination of root architecture.